Fungsi Konstitusional DPR dalam Perspektif Hak Rakyat: Antara Representasi dan Resistensi - Wijaya, Muhamad Arya (CV. Era Digital Nusantara, 2025)
The House of Representatives or DPR (Dewan Perwakilan Rakyat) is a constitutional body with primary functions of representing the people, enacting legislation, conducting oversight, and approving the budget. However, political dynamics and various controversial policies in recent years have led to significant public resistance. This research employs a qualitative approach, incorporating policy analysis methods, to examine the role of the House of Representatives from the perspective of people's rights, including factors that strengthen and weaken its functions. The study results indicate that although the House of Representatives has excellent potential in realizing public aspirations, weaknesses in integrity, transparency, and public participation have eroded public trust in this institution. Digitizing the legislative process, strengthening accountability, and providing continuous political education are recommended as strategies to optimize the role of the House of Representatives. This research confirms that strengthening the House of Representatives' function is key to achieving more responsive, inclusive, and just democratic governance in Indonesia.